Global Research Trends in Pediatric Trauma From 1968 to 2021: A Bibliometric Analysis - Ahmad, Tauseef; Hua, Linlin; Khan, Muhammad; Nabi, Ghulam; Khan, Suliman; Çinar, İlgün Özen and , Haroon and Jalal, Sajid and Baig, Mukhtiar and Jin, Hui and Wang, Xiaoyan (Frontiers in Pediatrics, 2021)
Introduction: Every year, millions of children die from preventable causes worldwide. According to World Health Organization, injuries are the leading cause of disability and death among all age groups below 60 years. Aim: This study aimed to evaluate the global research outcomes and trends, and some key bibliometric indicators in pediatric trauma. Methods: A descriptive bibliometric analysis study was designed. On June 14, 2021, an electronic search was performed in the Web of Science Core Collection database using the potential searching keywords “Pediatric AND Trauma” in the title field without any limitations. The search was performed using the Boolean search query method. The data were downloaded in plaintext and comma-separated values format. The required graphs were generated using OriginPro 2018. Furthermore, the data were transferred to HistCite™ software for bibliometric analysis. In addition, the obtained data were plotted for network visualization mapping using VOSviewer software version 1.6.15 for windows. Results: A total of 2,269 documents were included in the final analysis. The included documents were authored by 7,894 authors and published in 395 research and academic journals, mainly in the English language (n = 2,222). The main document types were articles (n = 1,276, citations = 18,244), and meeting abstracts (n = 331, citations = 19). Pediatric (n = 2,269) and trauma (n = 2,257) were the most widely used keywords. The most productive year was 2019 (n = 184, citations = 527). The most prolific author was Upperman JS (n = 29, citations = 202). The most attractive journals in pediatric trauma research were The Journal of Trauma and Acute Care Surgery (n = 290, citations = 5,199) and the Journal of Pediatric Surgery (n = 256, citations = 5,088). The most active institute was the University of California System (n = 110). The most dominant country was the United States of America (USA) (n = 1,620, citations = 22,983). The USA and Canada had the highest total link strength, 103 and 70, respectively. Conclusion: This study provides a comprehensive overview of research output in pediatric trauma. The USA continues to dominate scientific research and funding in pediatric trauma. Findings of the current study will help the researchers and clinicians to understand the recent achievements and research frontiers. Collaborative research initiative needs to be established between institutions in developed and developing countries and among researchers.